Case comment: estimating the economic value of the loss of a chance: a re-examination of Chaplin v. Hicks. (30th May 2018) - Miao, Weiwen; Gastwirth, Joseph L
Abstract: Although the Chaplin v. Hicks case was decided in 1911, it continues to be widely cited in law reviews and legal decisions because the case established the right of individuals to be compensated for the 'loss of a chance' in contract law. This 'loss of a chance' doctrine continues to be accepted in the UK and commonwealth nations in cases involving a breach of a contract in commercial law. The concept has also been accepted in medical malpractice cases in some states in the USA, but has not been widely adopted in commonwealth countries. While several methods have been developed to estimate damage in medical malpractice cases, relatively little attention has been devoted to methods for estimating the economic value of a lost chance in contract law. This case comment revisits the Chaplin v. Hicks case and uses simulations from several probability models to provide estimates of the amount of compensation due to Ms. Chaplin. All the estimates of the expected loss are significantly higher than the court's award of £100. The method of using probability models to estimate appropriate damages can be applied to other 'loss of a chance' cases.